Moderating Gender in Work From Home Policy Implementation on State Civil Apparatus Performance using Multigroup Analysis - Setyarini, Trisna; Wanto, Alfi Haris; Sentanu, I Gede Eko Putra Sri (Jurnal Borneo Administrator, 2024)
The WFH (Work from Home) policy has significantly changed the work landscape, particularly within governmental institutions. As organizations grapple with implementing this policy, they must navigate newfound disruptions and adapt to a new way of working. Understanding how this policy is executed sheds light on its impact on employee performance and whether the implemented work system is suitable. This study analyzed the relationship between WFH policy implementation and various factors such as work productivity, worklife balance, and overall apparatus performance, with a subsequent examination of gender moderation. Data were collected through a Google forms survey from January to February 2023, targeting all East Java Region's BPS (Central Bureau of Statistics) Regency/City personnel. Results indicate that the WFH policy enhances employee performance and productivity, both directly and indirectly. However, it also appears to diminish work-life balance. Overall, no significant differences are observed between genders regarding the implementation of WFH, whether in terms of performance, work productivity, or work-life balance, either directly or indirectly. The WFH policy emerges as a viable solution, particularly during the pandemic, offering workplace flexibility and ensuring employee health security